ผลของขนาดพอลิเมอร์และความเข้มข้นของไคโทซานต่อการเติบโตและผลผลิตของผักสลัดพันธุ์บัตเตอร์เฮด Lactuca sativa L. Butterhead และการแสดงออกของยีนที่ตอบสนองต่อไคโทซาน - กานต์สินี หังสพฤกษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The addition of oligomeric chitosan or polymeric chitosan with 80% degree of deacetylation (O80 or P80) at the concentrations of 5, 10, or 20 mg/L, into modified Hoagland nutrient solution enhanced growth of ‘Butterhead’ lettuce (Lactuca sativa L. ‘Butterhead’). The best productivity enhancement by chitosan was detected when 5 mg/L O80 was added to the nutrient solution. After growing for 45 days in the netted greenhouse under natural light, the harvested lettuce showed 8.46-17.91% increase in fresh weight, compared to the control plants, which were grown in nutrient solution without chitosan addition. They also showed the increase in leaf number and dry weight. After storage at 8°C for 10 days, Butterhead lettuce which treated with 5 mg/L O80 could maintain higher fresh weight, when compared to those control plants and showed the highest score of overall appearance. Moreover, chitosan O80 5 mg/L was selected for studying fresh weight, dry weight, ascorbic acid, photosynthetic pigment and fiber of this lettuce by growing in nutrient film technique (NFT) system. The results showed that 5 mg/L O80 increased fresh weight, dry weight and ascorbic acid content. However, chitosan O80 5 mg/L did not affect ribulose-1,5-bisphosphate carboxylase/oxygenase large subunit (rbcL) gene expression within 2 days of chitosan treatment. These data indicated that the appropriate use of chitosan molecule and concentration can efficiently enhance Butterhead lettuce productivity.